Canine vertebral screw and rod fixation system in dogs - Mohd Asri, Murshidah; Seng Fong, Lau; Radzi, Rozanaliza; Mazlan, Mazlina; Lewchalermwong, Pakthorn; Meij, Björn; Shafie, Intan Nur Fatiha (University of Chulalongkorn, 2022)
Bone plates and screws are often recommended to fix vertebral fracture and luxation in dogs although several complications had been reported. The canine vertebral screw and rod fixation (CVSRF) system, a device tailored for the canine spine, is a modified system from the human pedicle screw. This study aimed to determine the optimal corridor implantation of CVSRF and to investigate the potential trauma to the vertebrae and spinal cord in medium-sized dogs. Two screws of 16 mm and 20 mm and rods of 40 mm and 45 mm in length were inserted into the pedicles of L1 and L2 in six dogs. Safe implantation angles for 16 mm screw were 52.67° ± 10.40ºand 58.59° ± 7.72ºat L1 and L2, respectively. The angle of the 20 mm screw at L1 was recorded at 56.03°±5.34ºand 55.67° ± 2.89ºat L2. No gross and histological lesion was found on the spinal cord and vertebrae although minimal microfractures of the vertebrae were observed histologically. Findings from this study suggest that CVSRF is feasible for medium-sized dogs using 16 mm screws, however, a long-term study is required to determine the stability and durability of the system.